Plastic surgical techniques in the fifteenth century by Serafeddin Sabuncuoglu. - (:unkn) unknown (My University, 1997)
Serafeddin Sabuncuoglu (A.D. 1385-1468) is the author of the first illustrated surgical textbook in the Turkish-Islamic literature, namely, Cerrahiyet-ül Haniyye (Imperial Surgery). A pioneer in all fields of surgery. Sabuncuoglu developed numerous original techniques. He was a keen observer and inventor and a prolific writer who combined his fortune with knowledge of his era. He described a mass reduction procedure for the management of gynecomastia, probably one of the first attempts at reduction mammaplasty. He gave detailed descriptions of different eyelid pathologies and their surgical managements. The aim of this study is to investigate the contributions of this remarkable pioneer to the field of plastic surgery.